Medical Research from Realism to Abstractism: “Everything we Call Real is Made of Things we cannot Call Real” (Niels Bohr, 1885-1962) - Faaiz Alhamdani (Public Health, 2025)
During the last 2 decades, the medical research underwent a gradual transition from purely quantitative research (post-positivist) to endorse qualitative research (interpretivist) par-adigm. This article tries to shed a light on this transition and use fine art examples as analogy. For the sake of clarification it is important to explain some of the terms used in this article for readers whom their interest might be out of the scope of qualitative research or fine art.